P274 An unexpected disease in an infant with pancytopenia and pulmonary abscess: glycogen storage disease type 1b. (6th June 2017) - Yahşi, Aysun; Erat, Tuğba; Özdemir, Halil; Kara, Tuğçe Tural; Erol, Reyhan; Eminoğlu, Fatma Tuba; Ince, Elif; Çobanoğlu, Nazan; Fitoz, Suat; Doğu, Figen; Ince, Erdal; Çiftçi, Ergin
Abstract : 2.5-month-old boy had presented to another hospital with the complaints of wheezing and groaning. Thoracic CT of the patient revealed a heterogeneous, irregular lesions measured as 53 × 40 mm in size at the right hilar region. In addition; anaemia and neutropenia was detected. The patient had been referred to our hospital. Parents of the patient had cross-cousin marriage. In his physical examination; respiratory sounds were decreased in the middle and lower right lung, hepatomegaly (8 cm) and splenomegaly (8 cm) were detected. The whole blood count revealed a haemoglobin level of 6.1 g/dL, a white blood count of 8800/mm³ (total neutrophil count: 540/mm³), and a platelet count of 171.000/mm³. Blood glucose was 88 mg/dL, aspartate aminotransferase (AST) was mildly elevated (59 IU/mL). CT showed irregular soft tissue mass containing hypodense necrotic areas. Necrotizing pneumonia with abscess development was thought. Staphylococcus aureus was isolated in bronchoalveolar lavage collected with bronchoscopy. At the 4th day of treatment, pancytopenia was increased. Neutrophil functions, lymphocyte count and activity were normal and no chronic granulomatous disease gene and HAX-1 gene mutation was detected. Since neutropenia continued, GCSF was initiated. Hypertriglyceridemia (661 mg/dL) was found in lipid panel which was examined because of glycogen storage disease suspected due to parental consanguinity, neonatal hypoglycemia, hepatosplenomegaly and the apperance of the patient phenotypically as a doll face. Lactic acid level was found to be high (37 mg/dL), and uric acid value was at the upper limit (7 mg/dL). Compensated metabolic acidosis was observed in the blood gas. Hypoglycemia (32 mg/dL) was detected towards morning in the patient whom blood glucose was monitored. Homozygote c.1042_1043 delCT mutation was detected in the SLC37A4 gene of the patient which was considered to GSD 1b. When presenting our case, we aimed to make a contribution to early diagnosis and treatment by emphasising that GSD 1b disease should be considered in differential diagnosis even there is no symptomatic hypoglycemia in patients and particularly in often-fed infants presented with severe infection picture accompanied by hepatosplenomegaly and neutropenia and/or pancytopenia.